Self-actuated biomimetic nanocomposites for photothermal therapy and PD-L1 immunosuppression - Li, Wenxin; Li, Fen; Li, Tao; Zhang, Wenyue; Li, Binglin; Liu, Kunrui; Lun, Xiaoli; Guo, Yingshu (Frontiers in Chemistry, 2023)
Biomimetic nanocomposites are widely used in the biomedical field because they can effectively solve the problems existing in the current cancer treatment by realizing multi-mode collaborative treatment. In this study, we designed and synthesized a multifunctional therapeutic platform (PB/PM/HRP/Apt) with unique working mechanism and good tumor treatment effect. Prussian blue nanoparticles (PBs) with good photothermal conversion efficiency were used as nuclei and coated with platelet membrane (PM). The ability of platelets (PLTs) to specifically target cancer cells and inflammatory sites can effectively enhance PB accumulation at tumor sites. The surface of the synthesized nanocomposites was modified with horseradish peroxidase (HRP) to enhance the deep penetration of the nanocomposites in cancer cells. In addition, PD-L1 aptamer and 4T1 cell aptamer AS1411 were modified on the nanocomposite to achieve immunotherapy and enhance targeting. The particle size, UV absorption spectrum and Zeta potential of the biomimetic nanocomposite were determined by transmission electron microscope (TEM), Ultraviolet-visible (UV-Vis) spectrophotometer and nano-particle size meter, and the successful preparation was proved. In addition, the biomimetic nanocomposites were proved to have good photothermal properties by infrared thermography. The cytotoxicity test showed that it had a good killing ability of cancer cells. Finally, thermal imaging, tumor volume detection, immune factor detection and Haematoxilin-Eosin (HE) staining of mice showed that the biomimetic nanocomposites had good anti-tumor effect and could trigger immune response in vivo. Therefore, this biomimetic nanoplatform as a promising therapeutic strategy provides new inspiration for the current diagnosis and treatment of cancer.